HEALTH CONDITIONS OF THE PRISON SECURITY AGENT RELATED TO WORK ACTIVITIES. - Rodrigues Campelo, Andréia Maciel; Alves Ferreira Pereira, Marleth; Menezes de Berrêdo, Valéria Cristina; da Silva Santos, Deborah Aparecida; Salles da Silva, Michele; de Mello Bergamo, Vinicius (Revista de Pesquisa: Cuidado é Fundamental)
Objective: To analyze the physical and mental health conditions of the security agents of a penitentiary in the Municipality of Rondonópolis-MT related to labor activities. Methods: this is a descriptive study of a quantitative nature carried out in a penitentiary in the State of Mato Grosso. The data were collected in the months of May and June of the year 2017, through a questionnaire with closed questions. The analysis of the data used the statistics organized in tables. Results: in this study, 43 respondents were interviewed, aged between 35 and 40 years. Data analysis demonstrated that these professionals consider that unhealthy working conditions encourage physical, psychological and behavioral changes, as well as provide stress for this category. Conclusion: the results show that the working conditions imposed on the workers studied influence the health-disease process, which can result in physical, mental and social problems.